38 IMPROVEMENT IN FATIGUE IN FIBROMYALGIA SYNDROME WITH PROVIGIL (MODAFINIL) TREATMENT: REPORT OF THREE CASES AND DISCUSSION. Issue 1 (1st January 2007) - Gill, H.; Majithia, V.
Abstract : Introduction: Fibromyalgia syndrome (FMS) is a disorder characterized by widespread muscloskeletal pain, stiffness, nonrestorative sleep, and fatigue. These patients have significant and unremitting fatigue, but currently none of the available medicines work well for its treatment. Modafinil has been used in other chronic syndromes associated with fatigue, such as multiple sclerosis and a few cases of FMS. Its use is indicated in narcolepsy and shift work sleep disorder (SWSD), and it is used as an adjunctive therapy for obstructive sleep apnea/hypopnea syndrome (OSAHS). Case Series: We used modafinil in three patients with FMS who had severe fatigue and report our experience here. All of the patients in this series were females (ages 53, 58, and 63 years), met 1990 American College of Rheumatology (ACR) criteria for FMS, and had severe/disabling fatigue. Modafinil was initially started at 100 mg/d in the morning and subsequently increased to 200 mg/d. Two of the three patients had an excellent improvement of fatigue and one had moderate improvement as measured by the Modified Health Assessment Questionnaire (MDHAQ) and visual analogue scale (VAS) performed serially at 0-, 3-, and 6-month intervals. In the first patient, fatigue decreased from 10/10 to 3 and 2 on VAS at 3 and 6 months and was followed for 24 months. In the second patient, fatigue decreased from 10/10 to 1 and 2 at 3 and 6 months on the VAS and was followed for 18 months. In the third patient, fatigue decreased from 9/10 to 5 and 6 at 3 and 6 months on the VAS and was followed for 12 months. This improvement also translated into better overall well-being and functional status of these patients by their history and as measured by MDHAQ. All three patients were on modafinil 200 mg/d, with an average duration of follow-up of 18 months. Conclusion: This case series suggests that modafinil may be a pharmacologic option in the treatment of fatigue associated with FMS and may prove useful in treating this disabling and difficult to treat symptom. Further studies should be done to confirm the preliminary findings of this case series and other case reports.